Nexus between Crude Oil, Exchange Rate and Stock Market Returns: An Empirical Evidence from Indian Context - Raju, Guntur Anjana; Shirodkar, Sanjeeta; Marathe, Shripad Ramchandra (International Journal of Energy Economics and Policy, 2021)
Crude oil is considered as a major resource of any developing country it may be either Oil importing or exporting countries. The present study examines the relationship between the Exchange rate, Crude oil and Stock market returns. The study analyse the monthly observations from 1st April 2003 to 31st March 2019 with the help of Co integration, Granger causality, Variance Decomposition. The overall findings of the study indicate a significant effect of Crude oil on USD/INR Exchange rate. Theoretically, an oil price shock may be transmitted as the collapse in Crude prices pushes down the domestic price of non-traded products and hence the real Exchange rate and returns from Stock Market. Keywords: Crude Oil, Exchange rate, Stock Market returns, Co-integration, Variance Decomposition JEL Classifications: E3, F31, Q4 DOI: https://doi.org/10.32479/ijeep.9897